Signatures Beyond Oncogenic Mutations in Cell-Free DNA Sequencing for Non-Invasive, Early Detection of Cancer - De, Subhajyoti (Frontiers in Genetics, 2021)
Screening for early detection of cancer saves lives, it is now routinely advocated for those at a high risk of developing certain types of cancer. Effective early cancer detection in public health settings requires a delicate balance - periodic screening should neither miss rapidly progressing disease nor fail to detect rare tumors at unusual locations; on the other hand, even a modest false positive rate carries risks of over-diagnosis and over-treatment of relatively indolent non-malignant disease. Genomic profiling of cell-free DNA from liquid biopsy using massively parallel sequencing is emerging as an attractive, non-invasive screening platform for early detection, which offers multiple potential advantages over the current standard of care based on computed tomography, tumor-specific antigen etc. While clinical cell-free DNA sequencing providers primarily reports oncogenic mutation status, additional molecular signatures related to potential tissue of origin, the extent of clonal growth, and malignant disease states can be learnt from the data – which in turn can help guide clinical management strategies for targeted follow-ups using imaging or molecular marker-based diagnostic platforms.